2023
DOI: 10.1108/ijoa-11-2022-3518
|View full text |Cite
|
Sign up to set email alerts
|

Confidence and coincidences in executive decision-making during periods of crisis

Simona Mormile,
Gabriella Piscopo,
Paola Adinolfi

Abstract: Purpose The purpose of this study, which is grounded in decision-making theory, is to explore whether the occurrence of meaningful coincidences can positively influence executive confidence during periods of crisis. Design/methodology/approach Through a qualitative study with 24 interviews, this study focuses on Italian hospitality facilities in the Campania Region of southern Italy to explore how an executive confidence led by meaningful coincidences can influence managerial decisions during crisis situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This is especially true in the case of executive decision making due to the highly risky stakes involved, and with each decision costing the involved organization in some way or form. This is evident from the studies such as [33] , where it explores how meaningful coincidences can boost executive confidence and improve related decision-making in crisis situations within the Italian hospitality industry, filling a gap in existing literature on crisis management, whereas [34] investigates the relationship between CEO financial expertise and decision-making in 270 Chinese non-financial firms from 2005 to 2021, highlighting the increasing importance of financial literacy for strategic decision-making and long-term competitiveness in a dynamic economic environment. Some related research can also be found in [35 , 36] .…”
Section: Additional Informationmentioning
confidence: 81%
“…This is especially true in the case of executive decision making due to the highly risky stakes involved, and with each decision costing the involved organization in some way or form. This is evident from the studies such as [33] , where it explores how meaningful coincidences can boost executive confidence and improve related decision-making in crisis situations within the Italian hospitality industry, filling a gap in existing literature on crisis management, whereas [34] investigates the relationship between CEO financial expertise and decision-making in 270 Chinese non-financial firms from 2005 to 2021, highlighting the increasing importance of financial literacy for strategic decision-making and long-term competitiveness in a dynamic economic environment. Some related research can also be found in [35 , 36] .…”
Section: Additional Informationmentioning
confidence: 81%
“…Based on the study by Mormile et al (2023) on "Confidence and coincidences in executive decision making during periods of crisis," future research can focus on several key areas.…”
Section: Future Research On Nonrational Decision-makingmentioning
confidence: 99%
“…Based on the study by Mormile et al (2023) on “Confidence and coincidences in executive decision making during periods of crisis,” future research can focus on several key areas. First, investigating the long-term effects of meaningful coincidences on executive decision-making would provide insights into the sustained impact of these coincidences over time.…”
Section: Future Research On Nonrational Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations